Light-control of Liquid Crystal Alignment from Vertical to Planar - Hegde, Gurumurthy; Ata Alla, Rasha; Komitov, Lachezar (AIP Publishing LLC., 2013)
Continuous or discontinuous transition from vertical to planar alignment was found in nematic cells,containing polyimide alignment layer exposed to linear polarized UV light, depending on whether the alignment layer was mechanically rubbed or not prior the illumination. The polyimide material is designed originally to promote vertical alignment when deposited onto the inner cell substrates’ surface. The mechanism behind these observations is complicated. It includes inclination of the alkyl side chains of the polyimide alignment layer towards the rubbing direction and the bond breaking process due to UV illumination which are considered as the key factors for occurrence of such alignment transition.